Due Process in a Search of Electronic System by Patrol Officer - Nawa, Fridolin; Veronica, Shierren; Samudra, Anton Hendrik; Setiawan, Peter Jeremiah (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2022)
The criminal justice system provides the legal framework for a fair and justifiable search. A search is justifiable when there is a search warrant or strong suspicion of crime by the police. However, instances of coercion and arbitrary acts by law enforcement officers still occur in practice, as seen in the case portrayed in East Jakarta. While this case does not represent the behaviour of all law enforcement officers, the standard for a fair search must be enforced. This article discusses the legal procedures for conducting a justifiable search of electronic systems suspected to be a tool of crime and evaluates whether such a search would violate the right to privacy. The article provides an academic discussion and evaluation of criminal law procedures in practice, using doctrinal research to scrutinize the provisions within the Electronic Information and Transaction Law (EITL), Criminal Procedure Law (CPL), and Personal Data Protection Law (PDPL) to determine the parameters of a justifiable search of an electronic system that conforms to the due process of law. Additionally, a comparison between the PDPL and the UK GDPR, as well as the 2018 Data Protection Act, was conducted to evaluate the privacy provisions in a search activity by law enforcement officers. The research finds that not every patrol officer has the justified measures to conduct a search on an alleged person, unless there is enough probable cause as stipulated in the CPL. Searches of civilian cell phones that are not in accordance with CPL, EITL, and PDPL should be considered illegal, and the officer who conducts them should be held accountable, both legally and ethically.